The Role of Baitul Maal Wa Tamwil (BMT) Indragiri in Improving Sharia Financial Literacy For MSME: a Maqashid Syariah Perspective - Yudi; Tasriani; Devi Megawati (LP2M IAIN Palopo, 2026)
Sharia financial literacy is an important factor in improving the understanding of MSME regarding financial management in accordance with sharia principles. The low level of understanding of the community and MSME regarding the products and services of sharia financial institutions can affect the utilization of financial institutions in supporting economic activities and business development. This study aims to analyze Baitul Maal Wa Tamwil (BMT) Indragiri in improving sharia financial literacy for MSME, analyze the supporting and inhibiting factors of efforts to improve sharia financial literacy for MSMEs in Rengat District, and analyze the role of BMT in improving sharia financial literacy reviewed from the perspective of maqashid sharia. The method used in this study is qualitative, and this research was conducted on Jalan Sultan Kompleks Indragiri Islamik Center, Kp Dagang Village, Rengat District, Indragiri Regency, Riau Province. The data sources in this study are primary data and secondary data, data collection techniques are interviews. Based on the research results, it was found that in improving Islamic financial literacy, BMT Indragiri has implemented a management plan consisting of planning, organizing, directing (actuating), and monitoring (controlling). The most supporting factor for BMT Indragiri's success in improving Islamic financial literacy is the increasing level of public awareness of the use of Islamic contracts. The factors that hinder BMT Indragiri in improving Islamic financial literacy are internal and external obstacles. BMT Indragiri consistently integrates the values ​​of maqashid sharia in every financial literacy activity, especially the values ​​of justice (al-'adl) and welfare (al-maslahah). Meanwhile, the value of welfare (al-maslahah) is reflected in the literacy orientation that emphasizes not only increasing knowledge, but also on empowering the people's economy. Overall, the level of implementation of maqashid sharia by MSME fostered by BMT Indragiri is in the fairly good category, especially in the aspects of financial transactions and business management.